The chapters of the wisdom of my Lord Mani. - Gardner, Iain.; BeDuhn, Jason.; Dilley, Paul C. (Nag Hammadi and Manichaean Studies, 2018)
The Chapters of the Wisdom of My Lord Mani , a Coptic papyrus codex preserved at the Chester Beatty Library in Dublin, describes Mani's mission, teachings and debates with sages in the courts of the Sasanian empire during the reign of Shapur I; with an extended account of his last days and death under Bahram I. The text offers an unprecedented new source for the history of religions in Late Antiquity, including interactions of Manichaean, Zoroastrian, Christian, Jewish, and Buddhist traditions in Iran, remarkably transmitted into the Mediterranean world as part of Manichaean missionary literature. This is the first of four fascicles constituting the editio princeps , based on enhanced digital and multispectral imaging and extended autoptic study of the manuscript.